Ácidos grasos, fermentación ruminal y producción de metano, de forrajes de silvopasturas intensivas con leucaena (2016)
ABSTRACT: The aim of this study was to evaluate the effect of forages on the long chain fatty acids, ruminal fermentation, and methane production in an intensive silvopastoral system of Leucaena leucocephala. This study was developed in the laboratory NUTRILAB-GRICA, of the Faculty of Agricultural Sciences, University of Antioquia, Medellin-Colombia, in July 2013. The study was carried out by the in vitro gas production technique using grasses (C. plectostachyus and/or M. maximus cv. Tanzania) and leucaena (L. leucocephala) as substrate of fermentation, alone or with their combinations, with 70:30 forage:concentrate ratio and 56:14 grass: leucaena ratio for a total of seven treatments. No forage effect (p>0,05) on the conjugated linoleic fatty acid content (CLA, C18:2 c9t11) or rumenic acid, in the digesta was found. The inclusion of 14% of leucaena increased the content of linoleic (C18: 2 c9, 12) and linolenic (C18: 3 c9, 12, 15) acids in food and transvaccenic (TVA, C18: 1 t11), stearic (C18: 0), linoleic and linolenic acids in the digesta (p <0.05), and did not affect the kinetics of fermentation, digestibility of dry matter, pH, total and ratio volatile fatty acids, nor reduced methane production. Grasses, C. plectostachyus and M. maximus had a similar behavior in the evaluated variables (p>0.05). Silvopastoral systems could be an option to increase the beneficial fatty acids in milk.